Stress analysis induced by various implant distributions of implant supported class {u2160} obturators - Ahmed Abdelreheem Moneeb; Alaa Aboulela; Amr Abdullah Radi; Hussien Elcharkawi (Cairo : Ahmed Abdelreheem Moneeb, 2013)
Objective: to compare and evaluate the stress distribution to the supporting structures around three implants supporting an obturator under vertical loading using strain gauge technology in three various implant distributions. Methods: the experiment was carried out on an aramany class {u2160} maxillofacial defect of an edentulous acrylic model, with five installed implants equally distributed in the edentulous non defect side
Thesis (M.Sc.) - Cairo University - Faculty of Oral and Dental Medicine - Department of Prosthodontics
Issued also as CD
Keywords: Class {u2160} Aramany maxillary defect; Strain gauge analysis; Vertical load application